Graphical models for security : second International Workshop, GraMSec 2015, Verona, Italy, July 13, 2015, Revised selected papers /: second International Workshop, GraMSec 2015, Verona, Italy, July 13, 2015, Revised selected papers. (2016) - Unknown
No abstract available